2011
DOI: 10.1097/01.naj.0000405060.13022.b7
|View full text |Cite
|
Sign up to set email alerts
|

Care of the Suicidal Pediatric Patient in the ED: A Case Study

Abstract: algorithm, Asperger's syndrome, attempted suicide, bullying, emergency, emergency department, patient safety, pediatrics, pediatric suicide, suicide, suicide screening, triage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A small number of case studies (n = 3) were reviewed (see Table 4) to gauge whether similar trends were reported anecdotally in case studies as were observed in clinical studies. Not surprisingly, all of the individuals in the reported case studies were male; two adults (Hare, 1997;Spencer et al, 2011) and one child of elementary school age (Schmid, Truog, & Damian, 2011). In terms of suicidal behaviors, all of the participants either threatened or engaged in self-harm/suicide attempts using knives (e.g., hunting knife, butcher knife) or sharp objects (i.e., broken glass).…”
Section: Case Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…A small number of case studies (n = 3) were reviewed (see Table 4) to gauge whether similar trends were reported anecdotally in case studies as were observed in clinical studies. Not surprisingly, all of the individuals in the reported case studies were male; two adults (Hare, 1997;Spencer et al, 2011) and one child of elementary school age (Schmid, Truog, & Damian, 2011). In terms of suicidal behaviors, all of the participants either threatened or engaged in self-harm/suicide attempts using knives (e.g., hunting knife, butcher knife) or sharp objects (i.e., broken glass).…”
Section: Case Studiesmentioning
confidence: 97%
“…Spencer et al (2011) account the suicidal acts of a man, who attempted suicide following interpersonal conflicts at his place of employment. Finally, the case report of a school-aged child details suicidal ideation related to being bullied at school (Schmid et al, 2011). Three important points are highlighted within these case reports: (a) methods used by individuals with ASD involve potentially lethal means (e.g., sharp objects and alcohol); (b) all cases had psychiatric diagnoses in addition to ASD, and (c) interpersonal issues appear to act as a trigger in the suicidal acts of individuals with ASD.…”
Section: Case Studiesmentioning
confidence: 99%
“…More recently, there has been growing evidence of an evolving emergency nursing discourse that supports and encourages an empathetic approach to suicide prevention. Nurses need to provide empathetic care for all patients who present to ED with SRTB (Betz & Boudreaux, 2016; Heyland et al., 2018; Large, 2016; Schmid et al., 2011; Wilson et al., 2019). Often nurses are the first point of contact for patients in ED, and nurses need to create an emotionally safe place for patients to communicate their needs without feeling judged (Wilson et al., 2019).…”
Section: Discussionmentioning
confidence: 99%